2016
DOI: 10.1002/adfm.201504879
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Transdermal Vaccination Using Hyaluronan Nanocarriers and Laser Adjuvant

Abstract: Vaccines are commonly administered by injection using needles. Although transdermal microneedles are less-invasive promising alternatives, needle-free topical vaccination without involving physical damage to the natural skin barrier is still sought after as it can further reduce needle-induced anxiety and simply administration. However, this long-standing goal has been elusive since the intact skin is impermeable to most macromolecules. Here, we show an efficient, non-invasive transdermal vaccination in mice b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 62 publications
1
44
0
Order By: Relevance
“…[7071] Transdermal immunotherapy has been enabled by conjugating HA with antigenic peptides such as myostatin fragment [72] or ovalbumin. [73] HA can enhance the permeation of macromolecules to a greater degree than some small-molecule CPEs, [74] but not as much as some combinations of small-molecule CPEs. [42] …”
Section: Transdermal Drug Deliverymentioning
confidence: 99%
“…[7071] Transdermal immunotherapy has been enabled by conjugating HA with antigenic peptides such as myostatin fragment [72] or ovalbumin. [73] HA can enhance the permeation of macromolecules to a greater degree than some small-molecule CPEs, [74] but not as much as some combinations of small-molecule CPEs. [42] …”
Section: Transdermal Drug Deliverymentioning
confidence: 99%
“…Gonzalez-Aramundiz et al prepared protamine/LMW HA (162 kDa) NPs using a mild ionic cross-linking technique and showed that in vitro Ag (rHBsAg)-loaded anionic NPs (protamine/HA of 1:4, w/w) induced the secretion of cytokines including TNFα, IL-1α, and IL-6 by macrophages more efficiently than the cationic NPs (protamine/HA of 4:1), whereas in mice, by either intramuscular or intranasal administration, the cationic NPs induced more robust immune responses than the anionic NPs did, as proved by the higher levels of the IgG against the hepatitis B antigen in the cationic NP group, indicating that the protamine/HA NPs depending on physical features may be an effective VADS for delivering subunit HBV vaccines [74]. Kim et al using LMW HA (215 kDa) synthesized HA-OVA conjugates, which proved able to facilitate DC maturation in vitro and, after topical application to penetrate into the dermis in murine skins, efficiently induced secretion of the anti-OVA IgG levels in serum as well as IgA levels in bronchioalveolar lavage, which could promptly respond to an OVA challenge after 8 weeks rendering a strong immune-recall humoral response, especially, under the condition of pretreatment of the skin using nonablative fractional laser beams to save Ag dose, strongly supporting of the adjuvant role that LMW HA can play for developing the painless topical VADS [75].…”
Section: Hyaluronic Acid (Ha)-modified Liposomesmentioning
confidence: 81%
“…Kim et al combined transdermal vaccination using hyaluronan (HA) nanocarriers with NAFL to enhance the efficacy of transdermal vaccination. 54 HA is a natural macromolecule with intrinsic high permeability into the skin and was used as a carrier of a model antigen for noninvasive vaccination on the skin in this study. Conjugates of ovalbumin (OVA) and HA also facilitated endocytosis via HA receptor and induced maturation of DCs in vitro, providing an additional adjuvant-like effect.…”
Section: Laser Adjuvantmentioning
confidence: 99%